MISINTERPRETATION IN THE MEME OF WOMEN’S DECEPTION IS MORE POWERFUL THAN SATAN - Matsna, Afwi Nadia (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2023)
Social media provides a platform for the concise and creative framing of religious narratives, often incorporating captivating visual elements and synoptic explanations through memes. Nevertheless, employing memes to mediatize the Qur’an frequently results in misleading interpretations. This paper scrutinizes the misinterpretation of Yusuf: 28 and Al-Nisa’: 76 in a viral meme circulating on social media, which asserts that “the deceitfulness of women surpasses that of the devil.” Three key inquiries are posed: a) How are these two verses interpreted and presented in meme form? b) What factors contribute to the deviations from the original meaning? c) What impact does the mediatization of this Qur’anic verse in the meme have in fostering a negative perception of women? By leveraging Ahmad Rafiq’s Qur’anic reception and Gary R. Bunt’s cyber Islamic environments theory in conjunction with qualitative research methodologies, this study identifies a disparity in the meme’s interpretation of the Qur’anic verse when compared to traditional and contemporary tafsir (Qur’anic exegesis). The visual composition of meme content is intrinsically linked to the prevailing trend in digital information delivery, which prioritizes simplicity and leverages psychological factors through elements such as captions and color choices. Furthermore, this research underscores the implication that excessive mediatization can lead to distortions in religious narratives, as evident in these memes that employ Qur’anic verses to unfairly stereotype women. In reality, the depicted report conveys a profound cynicism, suggesting that the potential flaws of women are even more significant than those of the most vile creature, Satan.